(untitled) (Economics and region, 2018)
The article deals with resource savings in utilities sector cities, sources of financing of innovation activity. There are formulated approaches to strategic management innovative development utilities, processes resource savings in the context of innovation development. The author proposed financial incentive tools resource savings in public services communal economy of cities